Syphilis, The Great Mimicker, Presents As a Rare Case of Concurrent Hepatitis and Gastroparesis. Issue 6 (June 2019) - Shinn, Brianna; Kistler, Charles; Dhanekula, Raja Koteswar; Civan, Jesse
Abstract : ABSTRACT: Syphilis has been called "the great mimicker" given its ability to affect a wide variety of organs and subsequently present with a vast array of symptoms. The variability in clinical presentation seen in syphilis can make the diagnosis challenging. We describe a unique presentation of syphilis manifesting as hepatitis and gastroparesis. To our knowledge, this is the first case report with simultaneous hepatic and gastric involvement.